1983
DOI: 10.1159/000194564
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Size and Energy Metabolites in Five Separate Muscles from Patients with Chronic Obstructive Lung Disease

Abstract: The purpose of this study was to examine whether morphologic abnormalities in human respiratory muscles are related to increased airway obstruction. 43 patients who were undergoing thoracotomy for suspected neoplasm had biopsies taken from one or more of the following muscles: external intercostal (EXT), internal intercostal (INT), diaphragm (DIA), latissimus dorsi (LAT), and quadriceps femoris (LEG). Mean FEV1/FVC was 65% of predicted (range 43–90%). 21 of the 43 patients had a malignancy. Atrophy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
38
0
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 13 publications
8
38
0
1
Order By: Relevance
“…In the patient population, COPD has been demonstrated to induce variable alterations in fibre composition of peripheral skeletal muscles. Similar to the present investigation, HUGHES et al [10] and JAKOBSSON et al [25] demonstrated no differences in fibre composition of vastus lateralis muscle biopsies from COPD patients, and SATO et al [11] found no difference in fibre composition in biceps brachii muscle biopsies. In contrast, other investigators [4,6,7] have reported that COPD patients have a lower proportion of type I fibres and an elevation in the per cent of type II fibres in the vastus lateralis muscle.…”
Section: Potential Mechanismssupporting
confidence: 89%
See 3 more Smart Citations
“…In the patient population, COPD has been demonstrated to induce variable alterations in fibre composition of peripheral skeletal muscles. Similar to the present investigation, HUGHES et al [10] and JAKOBSSON et al [25] demonstrated no differences in fibre composition of vastus lateralis muscle biopsies from COPD patients, and SATO et al [11] found no difference in fibre composition in biceps brachii muscle biopsies. In contrast, other investigators [4,6,7] have reported that COPD patients have a lower proportion of type I fibres and an elevation in the per cent of type II fibres in the vastus lateralis muscle.…”
Section: Potential Mechanismssupporting
confidence: 89%
“…HUGHES et al [10] reported reductions in type II, but not type I fibres in vastus lateralis muscle biopsies from COPD patients. In contrast, two other investigations demonstrated reductions in both type I and type II fibre size in peripheral skeletal muscle biopsies from COPD patients [7,11].…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Muscle biopsies during rest periods are often used to assess muscle metabolism [4][5][6][7] , as is magnetic resonance spectroscopy (MRS) during exercise 8,9) . To assess muscle oxygenation, arterial and venous blood sampling are used [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%